2022
DOI: 10.3390/antiox11040727
|View full text |Cite
|
Sign up to set email alerts
|

Investigating a Curcumin-Loaded PLGA-PEG-PLGA Thermo-Sensitive Hydrogel for the Prevention of Alzheimer’s Disease

Abstract: In Alzheimer’s disease (AD), the most common cause of dementia, patients generally forget to take pills or skip medication due to side effects, affecting the treatment efficacy. In this study, we combined a poly(lactic-co-glycolic acid), (PLGA)-poly(ethylene glycol), and (PEG)-PLGA thermo-sensitive hydrogel with curcumin (PGC) to deliver an intramuscular injection that could continuously release curcumin and maintain it at a constant level in blood to prevent AD development or progression. We evaluated the dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Lin et al [ 57 ] evaluated the combination of PLGA-PEG-PLGA thermo-sensitive hydrogel with CUR (PGC) in preventing and decreasing the progression of AD. In vitro studies demonstrated that PGC did not exert cytotoxicity but had excellent anti-inflammatory and antioxidant properties and microglial modulation.…”
Section: Cur a Phenolic Compound Derived From Curcuma Longamentioning
confidence: 99%
“…Lin et al [ 57 ] evaluated the combination of PLGA-PEG-PLGA thermo-sensitive hydrogel with CUR (PGC) in preventing and decreasing the progression of AD. In vitro studies demonstrated that PGC did not exert cytotoxicity but had excellent anti-inflammatory and antioxidant properties and microglial modulation.…”
Section: Cur a Phenolic Compound Derived From Curcuma Longamentioning
confidence: 99%
“…This is the result of various parameters including enhanced mechanical characteristics and degradation of hydrogels in a finely tuned, highly controlled manner. The most frequently investigated natural polymers used for hydrogel preparation are chitosan, dextrin, lignin, hyaluronic acid, carrageenan, tannic acid, alginic acid, and collagen. Synthetic and semisynthetic polymers can also be used for hydrogel preparation . These polymers mainly include polyethylene glycol (PEG), poly lactic acid, poly lactic coglycolic acid (PLGA), and poly vinyl alcohol (PVA) as well as carboxymethyl cellulose (CMC), hydroxyethyl cellulose, hydroxypropyl cellulose, and hydroxypropyl methyl cellulose. Based on the monomers used for the preparation of the polymeric network, hydrogels may contain homo-polymeric, co-polymeric, or multi-polymeric networks. , While polymerization of a single type of monomers results in the formation of homo-polymeric networks, co-polymeric or multi-polymeric networks result from the polymerization of two or more types of monomers. , …”
Section: Introductionmentioning
confidence: 99%
“…The biocompatibility, swelling behavior, and low toxicity of hydrogels make them suitable candidates for biomedical applications including drug delivery. One of the major obstacles for drug development is the administration of hydrophobic drugs with low solubility in aqueous media . Considering the unique properties of hydrogels, this delivery system can be used as a promising vehicle for formulation of low soluble hydrophobic therapeutics. ,, This approach enables researchers and patients to apply these therapeutic agents via oral, topical or parenteral routes of administration …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations